Aphid wing induction and ecological costs of alarm pheromone emission under field conditions. - Eduardo Hatano (Public Library of Science (PLoS), 2010)
The pea aphid, Acyrthosiphon pisum Harris, (Homoptera: Aphididae) releases the volatile sesquiterpene (E)-beta-farnesene (EBF) when attacked by a predator, triggering escape responses in the aphid colony. Recently, it was shown that this alarm pheromone also mediates the production of the winged dispersal morph under laboratory conditions. The present work tested the wing-inducing effect of EBF under field conditions. Aphid colonies were exposed to two treatments (control and EBF) and tested in two different environmental conditions (field and laboratory). As in previous experiments aphids produced higher proportion of winged morphs among their offspring when exposed to EBF in the laboratory but even under field conditions the proportion of winged offspring was higher after EBF application (6.84+/-0.98%) compared to the hexane control (1.54+/-0.25%). In the field, the proportion of adult aphids found on the plant at the end of the experiment was lower in the EBF treatment (58.1+/-5.5%) than in the control (66.9+/-4.6%), in contrast to the climate chamber test where the numbers of adult aphids found on the plant at the end of the experiment were, in both treatments, similar to the numbers put on the plant initially. Our results show that the role of EBF in aphid wing induction is also apparent under field conditions and they may indicate a potential cost of EBF emission. They also emphasize the importance of investigating the ecological role of induced defences under field conditions.